Graphical Visualization of STACK Response Analysis - Karin Landenfeld and Malte Eckhoff and Jonas Priebe (Zenodo : research shared, 2021)
STACK offers question types that enable open questions and differentiated feedback based on a response tree. A simple and clear way of analyzing the answers given would make it easier for lecturers to get information about the level of students’ knowledge. It would help to discover students’ misconceptions and offers the possibility to expand the response tree. In this article we would like to present our work on a graphical interactive visualization of the STACK Response Analysis.
Keywords: STACK; response tree analysis; feedback tree; graphical visualization